Comparative evaluation of Google Glass, Vuzix M100 & Epson Moverio BT-200 (International Journal of Engineering and Computer Science, 2017)
Smart glasses are wearable devices which have computing capabilities and are worn like a spectacles. This white paper provides a comparative study of top leaders in Wearable Glasses including key features, technical specification comparison and gives some insights into possible challenges during adoption. This paper also highlights the typical challenges faced by developers while developing applications for such eyewear.